Sovereign default and the euro - Karl Whelan (University College Dublin, UCD School of Economics, 2013)
The introduction of the euro meant that countries with sovereign debt problems could not use monetisation and devaluation as a way to prevent default. The institutional structures of the euro were also widely thought to prevent a country in difficulties being bailed out by other euro members or having its sovereign debt purchased by the ECB. Despite these restrictions, there was relatively little discussion about sovereign default in pre-EMU debates among economists and financial markets priced in almost no default risk in the pre-crisis years. The crisis has seen bailouts and bond purchases by the ECB but there has also been a sovereign default inside the euro and further defaults seem likely. The introduction of the euro was intended to bring greater stability by ending devaluations triggered by self-fulfilling runs on a currency. While this particular scenario can no longer happen, this paper discusses mechanisms whereby expectations that a country may leave the euro can lead to this outcome occurring.
Keywords: 330